Combination of Telmisartan with Cisplatin Controls Oral Cancer Cachexia in Rats. (5th December 2013) - Patel, Bhoomika M.; Damle, Deepak
Abstract : The objective of the present investigation was to study the effect of combination of telmisartan with cisplatin in oral cancer cachexia induced by applying 0.5% 4-nitroquinoline-1-oxide (4-NQO) in propylene glycol to tongue, thrice a week for 8 weeks. From 8th to 22nd week, cisplatin (0.23 mg/kg, i.v.) was administered once in three weeks and telmisartan (5 mg/kg/day, p.o.) was administered daily. 4-NQO produced significant decrease in food intake, body weight, hyperglycemia, dyslipidemia, hypertension, and bradycardia, worsened hemodyanamics, increased cachexia markers like insulin, C-reactive protein, and interleukin-6, and increased tumor markers like lactate dehydrogenase and γ -glutamyl transferase.Treatment with combination of telmisartan with cisplatin produced significant increase in food intake and body weight and controlled hyperglycaemia and dyslipidemia, preserved hemodynamic function, and decreased the cachexia markers while cisplatin alone did not produce any increase in food intake and body weight. Further, the combination of telmisartan with cisplatin significantly reduced tumor marker levels. Combination of telmisartan with cisplatin prevented 4-NQO induced oxidative stress, hyperplasia and hyperkeratosis, premalignant dysplasia, and invasive squamous cell carcinoma in the tongue. Our data suggests that combination of telmisartan with cisplatin treatment is beneficial in controlling cancer cachexia. Telmisartan can be used as an add-on therapy with cisplatin or other traditional chemotherapeutic agents.